(untitled) - Miller, Michael (Indianapolis ; London, 2006)
Looking for "it"? That something different that will increase your eBay auction sale rates and selling prices? One of the most effective ways to generate more sales at high price-points is to create a more attractive, attention-getting auction listing. The easiest way to do this is through the use of templates that you can quickly populate with minimal effort and will maintain a style consistency across all of your auctions.
Keywords: Internet auctions,Internet marketing,Internet advertising,Kinh doanh qua mạng Internet,Tiếp thị qua mạng internet